2008
DOI: 10.1590/s0102-311x2008001400019
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of postpartum depression and early interruption of exclusive breastfeeding in the first two months of life

Abstract: This study evaluates the association between postpartum depression and interruption of exclusive breastfeeding in the first two months of life. Cohort study of 429 infants < 20 days of age to four primary health care units in Rio de Janeiro, Brazil. Interruption of exclusive breastfeeding (outcome) was defined as the introduction of water, other types of liquids, milk, or formulas or any food. Postpartum depression was assessed using the Edinburgh Post-Natal Depression Scale. Associations between variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
21

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 33 publications
5
34
0
21
Order By: Relevance
“…The above findings are in line with national and international studies that reinforce the negative effect of PPD symptoms on the duration of breastfeeding, associating them with early weaning (7,11,20,28) and with the interference of low self-confidence to breastfeed in the symptoms of PPD. (11,29) The symptoms related to guilt, anxiety, concern and distress are present in the daily events, more prevalent among women in this study, and associated with the PPD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The above findings are in line with national and international studies that reinforce the negative effect of PPD symptoms on the duration of breastfeeding, associating them with early weaning (7,11,20,28) and with the interference of low self-confidence to breastfeed in the symptoms of PPD. (11,29) The symptoms related to guilt, anxiety, concern and distress are present in the daily events, more prevalent among women in this study, and associated with the PPD.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies show a negative relation, evidencing the greater chance of puerperal women with depressive symptoms weaning their babies early, while others show that weaning is prior to the onset of depressive symptoms, and relate hormonal changes and psychological aspects as risk factors for PPD. (7)(8)(9) According to Bandura's theory of self-efficacy, the way individuals interpret their feelings tends to modulate their behavior. (10) In other words, the confidence of puerperal women in their ability to feed their child through breastfeeding (called maternal self-efficacy to breastfeed) tends to be compromised by the occurrence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…They are unable to perform routine activities of daily living, much less care for the newborn. Thus, it seems unlikely that a mother who lives under conditions of severe violence would find the right environment and, given her own priorities, perhaps the willingness to perform such a demanding task as breast-feeding (8,(34)(35) . Interestingly, the independent effect of SPVP could not be ratified once the variables related to child health, use of health services during the prenatal period and the degree of maternal self-esteem were introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, perinatal depression can have a considerable impact on mothers' childcare abilities. Previous studies [9,26] reported that mothers with postpartum depression were less likely to breastfeed their children and more likely to give up exclusive breastfeeding than mothers without depression. Breastfeeding can strengthen the immune system of the child and it has been shown that children who are not breastfed have more acute respiratory infections than those who are not [13].…”
Section: Discussionmentioning
confidence: 99%